Partially Isolated Dual Work Function Gate IGZO TFT With Obviously Reduced Leakage Current for 3D DRAMs - Yunjiao Bao; Gangping Yan; Lei Cao; Chuqiao Niu; Qingkun Li; Guanqiao Sang; Lianlian Li; Yanzhao Wei; Xuexiang Zhang; Jie Luo; Yanyu Yang; Gaobo Xu; et al. (IEEE Journal of the Electron Devices Society)
In this article, a partially isolated dual work function (PIDWF) gate In-Ga-Zn-O (IGZO) thin-film transistor (TFT) is proposed to reduce the off-state current (Ioff) obviously, which also provides a feasible integration method for stacking IGZO TFT on Si-based devices. It is found that compared with the general back gate IGZO TFT structure, the Ioff of the proposed IGZO TFT reduces from $2.57× 10{^{-}14 }$ A/ $μ $ m to $7.57× 10{^{-}16 }$ A/ $μ $ m, achieving two orders of magnitude improvement. This breakthrough has the potential to increase the retention time of DRAM applications by nearly 100 times. Moreover, the pronounced novel structure has mitigated parasitic capacitance, thereby leading to a notable 47.7% reduction in write latency within dynamic-random-access-memory (DRAM) circuits. The relevant operation mechanism is carefully demonstrated and verified by the simulation of the electric field and potential barrier results by technical computer-aided design (TCAD). Furthermore, the impacts of the dual gate work function level, the length, and the type of isolation dielectric between dual work function gates are systematically investigated. The results show that the off-state leakage is further reduced by increasing the difference of the work function levels between in dual gates, the dielectric length (LD) and using the isolation layer with a lower dielectric constant. The PIDWF gate IGZO TFT exhibits scalability and is capable of achieving an 84.6% reduction in leakage current even with ultra-short channel lengths, which offers a promising application for future 3D DRAM applications with little extra cost.